Retail Employees Wellbeing Model: Testing And Validation (Journal of Pharmaceutical Negative Results, 2023)
According to the Bureau of Labor Statistics. Between 2004 and 2014, employment of retail salespeople was predicted to grow at the same rate as the average for all occupations. The majority of job opportunities will arise as experienced individuals move on to other occupations or quit for other reasons. As retail sales continue to rise as a result of the rising population, more employment will be generated. A happy and engaged staff is the single most valuable asset in the modern economy. Positive emotions are currently the most researched topic. Employee satisfaction enhances practically all company results, according to extensive study conducted over the last decade. While retail executives can devise plans that painstakingly address market conditions, it will all be for naught if their people are disengaged. When it comes to the customer experience, research consistently backs up an overused but equally accurate adage: the employee experience dictates the customer experience. The study fills the research gap of proposing a conceptual wellbeing model for exclusively for retail employees. The study aims at testing the model with primary data and validate the model statistically. Finally, the conceptual model to be validated with the help of statistical tool confirmatory factor analysis (CFA) by presenting various dimensions of the wellbeing along with scale items.